EFFECT OF TIME AND TYPE OF FERMENTATION IN PHYSICAL AND CHEMICAL QUALITY OF COCOA (Theobroma cacao L.) NATIONAL TYPE - Rivera Fernández, Rubén Darío (2012)
This investigation had as an objective to evaluate types of fermenters and different times of fermentation used by cocoa producers from the central and north zone of Manabi province, Ecuador. Four fermenters were used: burlap sack, piles, wooden boxes and plastic vat with the ability to store 60 kilos of cocoa and fermentation times ranging from 2 to 5 days; a control was evaluated in addition (without fermentation). A Completely Randomized Blocks Design with additive factors arrangement with three replications was used. The data were analyzed using analysis of variance with Tukey test at 5% probability. Physical variables were analyzed: percentage of fermented, violet and slate (test cutting) grains; and chemical: polyphenols (photometry 760 nm), volatile acidity (steam stripping) and theobromine, caffeine (High Performance Liquid Chromatography, HPLC). The analysis of the results shows that the fermentation time unlike the type of fermenter, had an influence on the chemical and physical variables analyzed. The increased percentage of fermented beans and decreased violet grains occurred from the beginning until the end of fermentation. The chemical quality improves by reducing the concentration of alkaloid compounds and polyphenols, which impacts on the sensory characteristics of Nacional cocoa type. Of the fermenters and the times used by producers the best quality characteristics are presented between four and five days of fermentation in wooden boxes.